Sage (Salvia aucheri Bentham var. canescens Boiss. and Heldr.): Essential Oil Composition, Phenolics and Antioxidant Activity - Ozkan, Gulcan; Musa Ozcan, Mehmet; Y. Al Juhaimi, Fahad (Asian Journal of Chemistry, 2012)
The oil yield of dried plants (v/dw) (0.9 %) was determined by hydrodistillation. The essential oil composition of S. aucheri was analyzed by GC-MS. Thirteen compounds were identified, representing 93.95 % of the oil. The main constituents of the oils were: 1,8-cineole (44.43 %), camphor (19.04 %), a-pinene (6.38 %), borneol (5.64 %), (5.82), camphene (5.82 %) and b-pinene (5.12 %), respectively. 1,8-Cineole and camphor were the major components of S. aucheri. var. canescens. Antiradical activity (IC50) of the essential oil was established as 41.31 = μg/mL. In addition, phenolic components and antioxidant effect of extracts from S. aucheri were determined. The extract yield (%) of S. aucheri was 13.58. Main phenolic components (mg/100 g dried herb) were found as rosmarinic acid and carvacrol. Total phenolic content and antiradical activity (IC50) of the extract were also determined as 112.14 mg GAE/g extract and IC50 = 75.69 μg/mL.